Kształtowanie się ośrodków naukowo-badawczych andragogiki w Drugiej Rzeczypospolitej - Stopińska-Pająk, Agnieszka (Biuletyn Historii Wychowania, 2018)
The article shows the process of institutionalising andragogy in Poland. The author discusses the development of the first research institutions that gave raise to andragogical research in the Second Polish Republic (1918-1939). Special attention is given to academic centres, their representatives and the research projects they completed. The author shows also that while not widely popular, andragogy has an established position in university communities.